Synthesis of carbon nanomaterials on impregnated powdered activated carbon for removal of organic compounds from water / Haiyam Mohammed Abdalraheem Alayan - Haiyam Mohammed , Abdalraheem Alayan (2018)
Carbon nanomaterials (CNMs) are known to be superior to many other existing materials in terms of their remarkable properties. Despite of their strong adsorption affinity, they are limited in practical water treatment application for their difficulties involved in dispersion and separation. Moreover, wastewater contamination by toxic organic compounds has become a world-wide environmental concern because of the undesirable effects of these contaminants. Therefore, this research has been undertaken to explore the potential of directly growing CNMs on microscale support such as the powder activated carbon (PAC) to develop a novel CNM hybrid adsorbent for the removal of bisphenol A (BPA) and methylene blue (MB) from water. In this regard, chemical vapor deposition reactor (CVD) was used to synthesize CNMs on nickel impregnated powdered activated carbon from the decomposition of methane and acetylene. The Design of experiment (DOE) based on the response surface methodology (RSM) with the central composite design (CCD) was used to optimize the reaction temperature, reaction time and gases flowrates to obtain the maximum adsorption along with the maximum possible yield for CNM. The results demonstrated that the optimum conditions were different depending on the characteristics of the carbon precursor and the adsorbate under investigation. The optimized growth conditions for methane decomposition were found at 933 ºC, 20 min, and (H2/CH4) of 1.0. The produced CNM-PAC had multi-structures with groove-like features. Meanwhile, dense carbon nanotubes (CNTs) with tubular structures were dominant in the product obtained from the pyrolysis of acetylene at the optimum growth conditions of a reaction temperature of 550 ºC, a reaction time of 37.3 min, and a gas ratio (H2/C2H2) of 1.0. The physiochemical, and morphological properties of CNM-PAC samples at the optimal conditions were investigated using FESEM, TEM, EDX, BET, Raman spectroscopy, TGA, FTIR, and zeta potential. Adsorption studies for BPA and MB were carried out to evaluate the optimum removal conditions, kinetic, and isotherms. RSM-CCD experimental design was used to conduct the optimization studies and to determine the optimal conditions for the removal of BPA and MB by each selected adsorbent individually. The proposed models were optimized with respect to the operating pH, adsorbent mass and contact time as controlling parameters to correlate their effects on the removal efficiency of the pollutants and the adsorption capacity of the adsorbent. The optimization study showed that the maximum adsorption capacity for the removal of BPA and MB onto the CNM-PAC produced from methane was about 182 and 250 mg/g, respectively. The surface properties of CNT-PAC obtained from the pyrolysis of acetylene were modified by oxidative functionalization using two different methods: sonication with KMnO4, and with KMnO4/ H2SO4, however, the best removal of MB was obtained with the as-prepared CNT-PAC sample. The adsorption behaviors showed that the adsorption kinetics and isotherms were in good agreement with the pseudo second-order equation and the Langmuir isotherm model, respectively with a maximum adsorption capacity of about 175 mg/g.